285 A 'step' towards prevention of OA in physically active amputees using a novel foot prosthesis: a randomised controlled cross-over trial. (3rd March 2020) - Runciman, Phoebe; Cockcroft, John; Derman, Wayne
Abstract : Background: Individuals with unilateral transtibial amputation (UTTA) have higher external ground reaction forces in joints on their sound side during gait and this been linked to increased risk of osteoarthritis in these individuals. Objective: To describe the biomechanical characteristics in UTTA whilst using a novel, mechanically powered energy storing and returning (ESAR) ankle/foot prosthesis, compared with two control foot prostheses. Design: Randomised cross-over trial. Setting: Laboratory based study. Participants: 20 participants performed a standardized self-paced walking gait protocol using three different ankle/foot prostheses (novel ESAR foot (NOVEL), current gold standard ESAR (ESAR) foot and solid-ankle cushioned-heel (SACH) foot), in a randomised cross-over design. Assessment of risk factors: Three-dimensional kinematics of the lower body as well as ground reaction forces (GRF) were recorded with a ten-camera stereophotogrammetry motion capture system and three floor-imbedded force plates. Main outcome measurements: GRFs, external adduction moments (EAM) & ankle range of motion (ROM) Results: Despite similar peak GRFs between feet on the prosthetic side during walking (± 108% body weight), there were higher GRFs on the sound side during the load acceptance phase whilst participants used the SACH (126.3±11.5%) and ESAR (116.8±10.5%) feet, but not the NOVEL (108.7±9.3%, p<0.001). External Abduction Moments (EAM) observed on the sound side during loading was 0.55±0.3 Nm/kg, 0.6±0.3 Nm/kg and 0.7±0, 31 Nm/kg for the NOVEL, ESAR and SACH. The NOVEL had a sagittal ROM of 21.4±3.2 o, the ESAR 18.2±3.3 o and the SACH 8.4±2.3 o (p<0.001). Conclusions: The use of the NOVEL foot resulted in a similar loading/force pattern between prosthetic and sound sides in UTTA, which was not seen with the two other foot prostheses. Furthermore, participants demonstrated a better transition during double support, with improved ROM, and EAM, whilst using the NOVEL.